Study of non-family executives in Chinese family firms - Guo, Xin (2014)
85% of new family businesses failed during the first five year business running and only 30% of the rest survivals can transfer to the second generation of the business founders. In order to overcome the potential threat for family businesses, many owners of family business tried to employ nonfamily executives. Although a couple of reasons motivate those owners to employ nonfamily executives, there are also a number of constraints that prevent the decision. This situation becomes more complex within Chinese family business context, which is greatly influenced by Chinese culture, social norms, and other environmental factors. Thus, this study tries to explore the influential factors on Chinese family businesses employing nonfamily executives. The research conceptual framework is built based on previous studies. Three driving factors, including solving managerial and financing problems, lack of successor, and avoid internal conflict and make organisational change, are used to test the driving factors on Chinese family businesses. And six constraints, including high cost, conflict, internal resistance, incomplete labour market, poor capability, and low trust, are used to test the constraints of Chinese family businesses. In order to reach the research objectives, this study uses telephone interview to collect data from 16 respondents. 12 respondents are owner manager or shareholders of Chinese family businesses and 4 respondents are nonfamily managers. After qualitative data analysis of collected information from telephone interview, solving managerial and financing problems and lack of successor are identified as main driving factors, while high related cost, low efficient labor market, lack of trust, and few qualified nonfamily candidate are considered by interviewees as main constraint factors that hesitate Chinese family firms to employ nonfamily executives. Among those factors, solving managerial and financing problem are considered as the most important driving factor while lack of trust are considered as the most important constraints. This study also finds some hidden influential factors such as size and complexity of family firm and type of family business. But those factors need further study to testify.